ANALYSIS OF THE DEVELOPMENT OF THE ECONOMY OF THE REPUBLIC OF UZBEKISTAN ON THE BASIS OF REDUCING THE EFFECTS OF THE PANDEMIA - Tursunbaevich, Baykhonov Bahodirjon; Tursunalievich, Abdulhakimov Zuhrali; Khamidullaevich, Khalilov Nurillo; Ahmadjanovna, Solieva Gulbaxor (The journal of contemporary issues in business and government, 2021)
This article shows the ways to maintain the pace of development of the country’s economy in emergencies, taking into account the effects of globalization, the study of the country’s GDP in times of crisis, the study of the country’s economic potential under the influence of specific factors. is carried out with. These include tax reform aimed at liberalizing the foreign exchange market, increasing incomes and stimulating production, the gradual transition to medium-term budget planning, reducing the role of inflation targeting in the economy, the gradual privatization of state-owned enterprises and the introduction of market mechanisms. information on reforms.